2001
DOI: 10.1086/320603
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Deletion and Point Mutations of the Nuclear NDUFV1 and NDUFS1 Genes in Mitochondrial Complex I Deficiency

Abstract: Reduced nicotinamide adenine dinucleotide (NADH):ubiquinone oxidoreductase (complex I) is the largest complex of the mitochondrial respiratory chain and complex I deficiency accounts for approximately 30% cases of respiratory-chain deficiency in humans. Only seven mitochondrial DNA genes, but >35 nuclear genes encode complex I subunits. In an attempt to elucidate the molecular bases of complex I deficiency, we studied the six most-conserved complex I nuclear genes (NDUFV1, NDUFS8, NDUFS7, NDUFS1, NDUFA8, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(129 citation statements)
references
References 21 publications
4
124
1
Order By: Relevance
“…Anti-NDUFS1 was chosen here instead of anti-NDUFB8 because it produced better results (stronger signal) in immunofluorescent staining. NDUFS1 is a core subunit considered essential for complex I function [5]. Sections were deparaffinised in Histoclear and rehydrated in graded ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Anti-NDUFS1 was chosen here instead of anti-NDUFB8 because it produced better results (stronger signal) in immunofluorescent staining. NDUFS1 is a core subunit considered essential for complex I function [5]. Sections were deparaffinised in Histoclear and rehydrated in graded ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The clinical presentation of CI disorders can range from the neonatal period to adult onset, with symptoms including cardiomyopathy, liver disease and neurological disorders [55][56][57][58]. The most common clinical presentations include Leigh Syndrome, a multiple organ disorder with degeneration of the muscular, peripheral and central nervous systems [55,[59][60][61], fatal infantile lactic acidosis and other infancy/early childhood onset neuropathological disorders [44].…”
Section: Oxphos Complex Imentioning
confidence: 99%
“…Clinical hallmark signs of Leigh syndrome are brainstem dysfunction, symmetrical spongiform lesions in the brain, dystonia, spasticity, movement disorders, visual disturbances, nystagmus, ophthalmoparesis, ptosis, cerebellar ataxia, seizures, scoliosis, bulbar dysfunction and peripheral neuropathy that lead to biochemical signs of mitochondrial dysfunction including lactate elevation in different body fluids, Krebs cycle intermediates in urine and dysfunction of the mitochondrial respiratory chain in different tissues (Lake et al 2015). Mutations in the nuclear-encoded mitochondrial CI gene NDUFV1 [MIM 161015] have previously been reported by Schuelke et al (1999) in a patient with seizures, followed by a report by Benit et al (2001) in a patient with the same mutations as reported here and a clinical phenotype of Leigh syndrome and CI deficiency (Benit et al 2001;Schuelke et al 1999). This gene encodes a 51 kDa subunit of the flavoprotein portion of CI, containing NADH, flavin mononucleotide (FMN) and Fe-S-binding sites (Mimaki et al 2012).…”
Section: Introductionmentioning
confidence: 99%